Meningkatkan Penjualan Produk UMKM Di Desa Pugerwetan Melalui Kanal Media Sosial Dan Online Marketplace - HP, Agustin; Handayani, Yuniorita Indah; Ramadhanti, Dias Nastiti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2022)
Community Service is one of the pillars of the Tri Dharma of Higher Education, namely: education, research, and community service. One of the locations for community service carried out by the Mandala Institute of Technology and Science this year is Pugerwetan village where the majority of the population works as fishermen and the rest produce processed seafood into various superior products such as shrimp paste, condiment of the fermented shrimp, fish crackers, and dried fish. Many of these producers are hereditary business actors who still use traditional methods in the production process, as well as the marketing of their products. The purpose of this community service is to help producers to improve the quality of their products by using information technology. In this community service, our partners are shrimp paste producers and fish crackers producers in Pugerwetan village. Our service method is to provide public education, training, and advocacy regarding the importance of utilizing digital marketing through social media platforms and marketplaces as media for product sales promotion. The results of this Real Work Lecture are the use of social media platforms and marketplaces by shrimp paste and cracker producers as media for product sales promotion. Keywords: MSME, Pugerwetan, Social Media, Marketplace.